Firm performance and the quality of the provincial government in the COVID-19 pandemic era: Evidence from listed companies in Viet Nam - Duong Thi Chi; Nguyen Thu Hang (Asian Development Bank Institute (ADBI), 2024)
The main purpose of this article is to investigate whether firms experienced a decline in performance during the COVID-19 pandemic and the influence of the quality of local government on firm performance within the context of the pandemic, controlling for credit growth and firm characteristics variables. Firm performance was measured using return on equity (ROE), Tobin's Q, and firm growth while government quality was assessed through the proactivity of provincial leadership, business support services, and the growth of gross regional domestic product (GRDP). The findings reveal a significant difference in ROE, Tobin's Q, and firm growth before and during the pandemic, indicating that firm performance deteriorated during the COVID-19 pandemic. The lowest performance occurred in 2020, which showed the most significant influence of the pandemic. After controlling the dummy COVID-19 and interaction variables, we found that the proactivity of provincial leadership played an important role in mitigating the negative impact of the COVID-19 crisis on firm growth and ROE. Nevertheless, this study found no evidence of the impact of provincial governance measured by business support services and GRDP in the remaining regression models. It would seem that the proactive initiatives of local government can positively influence the market environment, leading to increased revenue (firm growth) and improved ROE. However, as the Tobin's Q index is determined by stock prices and linked to the stock market, the impact of local government is not substantial. Moreover, the current business support services provided by local government may not effectively meet firms' need to enhance performance, and changes in regional economic output (GRDP) during COVID-19 show no substantial influence on firm performance. Therefore, there is a need for broader support at the macro level, involving the active participation of the state and the Ministry of Finance.
Keywords: L25; E02; 330; firm performance; proactivity of provincial leadership; business support policy; GRDP; COVID-19 pandemic